Healthy Food Education and Training on Making Mocaf Flour for Women in Transmigrant Farmer Groups in Rasau Jaya Village: Edukasi Pangan Sehat Dan Pelatihan Pembuatan Tepung Mocaf Pada Wanita Kelompok Tani Transmigran di Desa Rasau Jaya - Hasria Alang; Syamsuri, Syamsuri; Khairillah, Yuyun; Adelia Triwahyuni; Annisa Nasywa Fahira (Universitas Lancang Kuning, 2024)
Cassava is a type of secondary crop which contains more complex carbohydrates than rice, making it safer and healthier. However, cassava tubers are not long-lasting and break down more quickly, so handling is needed to maximize the benefits while increasing the economic value of cassava. One way is by processing songkong into MOCAF flour. The aim of this PKM is to increase knowledge, understanding and skills for partners and at the same time as an effort to improve the partners' economy through optimizing the function of cassava into flour. The partners in this activity are women from the transmigrant farmer group in Rasau Jaya Village, totaling 30 people. The PKM method used is community empowerment through education and the ABCD method. The results of observations and tests showed that this activity was proven to increase participants' knowledge and enthusiasm. This is because education is provided in an interesting way and looks more real. This PKM activity was also successful because of positive support from partners